Flotation separation of chalcopyrite and pyrite via Fenton oxidation modification in a low alkaline acid mine drainage (AMD) system. (September 2022) - Ding, Zhan; Bi, Yunxiao; Li, Jie; Yuan, Jiaqiao; Dai, Huixin; Bai, Shaojun
Graphical abstract: Highlights: Fenton oxidation promoted selective flotation separation of chalcopyrite from pyrite, and the selectivity index was 5.69. This study unpacks a novel way for the clean utilization of AMD in the copper sulfide ore flotation. Multitude formation of Fe (III)–OOH (50.04%) and Fe2 (SO4 )3 (29.19%) depressed the pyrite flotation. A small amount of oxide/hydroxide species were formed on the chalcopyrite surfaces. Abstract: The selective flotation separation of pyrite and chalcopyrite, and the comprehensive utilization of AMD play a vital role in the cleaner production of copper sulfide ore. In this paper, flotation separation of chalcopyrite and pyrite via Fenton oxidation modification in a low alkaline acid mine drainage (AMD) system was investigated. The results of micro-flotation experiment displayed that the maximum recovery difference between chalcopyrite and pyrite was 74.6% at recommended test conditions. The artificial mixed-mineral flotation experiment further confirmed the desirable flotation separation of minerals. Zeta potential, FTIR spectra analysis, contact angle measurement and adsorption amount analysis results confirmed that the hydrophilic species caused by Fenton oxidation could seriously hinder the interaction between pyrite surfaces and EX collector. Whereas, the Fenton oxidation had feeble influence on the floatability of chalcopyrite. The XPS study indicated that Fenton oxidation significantly increased the contents of SO4 2- on pyrite surfaces, and the concentration of SO4 2- increased from 5.9% to 37.65%. Meanwhile, this modification promoted the deep transformation of Fe chemical states mainly from Fe(Ⅱ)-S to Fe(III)–OOH and Fe2 (SO4)3 . As a result, the contents of Fe(III)–OOH and Fe2 (SO4 )3 reached 50.04% and 29.19%, respectively. For chalcopyrite, a small amount of oxide/hydroxide species were formed during this processing, and the chalcopyrite can interact with EX collector effectively. Thus, flotation separation of chalcopyrite and pyrite via Fenton oxidation modification in a low alkaline AMD system mainly attributes to the significant differences in the number and species of hydrophilic species.